The Equality in the Discourse of Human Development (Andamios, Revista de Investigación Social, 2014)
This paper analyses whether the human development approach, as has been developed by the United Nations Program for Development (UNDP), includes in its basis the criterion of inequality associated with discrimination on the grounds of social stereotypes, such as gender, race, ethnicity, etc. From the human rights based approach, the text criticizes the prevalence of the concept of opportunity in the human development discourse, rather than capabilities or rights, considering that this notion is indebted to a meritocratic conception and not to an egalitarian one. The human rights based approach helps prioritize public goals for the people and vulnerable groups.
Keywords: Human development; capabilities; opportunities; human rights; discrimination